Metal grid contact design of four-terminal tandem solar cells - Sofia, Sarah E.; Ren, Zekun; Kanghah, Nasim Sahraei; Zhe, Liu; Buonassisi, Tonio; Peters, Ian Marius (2017 IEEE 44th Photovoltaic Specialist Conference, PVSC 2017, 2017)
Tandem solar cells comprised of a III-V material on Si offer a path to efficiencies exceeding 30%. The four- terminal architecture, in which each of the two sub-cells is electrically independent, allows for especially high energy yields, as it is not limited by current-matching. Each sub-cells' contacts cause optical and electrical losses, however; and a careful optimization is required to exploit the full potential of this architecture. In this study, we explore the potential efficiency gains of an example 21.3% GaAs-on-Si four-terminal tandem [1] by re-designing the metal grid contact geometry. We optimize and model the contact losses and predict a potential efficiency increase of 3.4% We demonstrate the importance of careful metal grid design and the benefits of using energy yield as a figure of merit when design contacts for a practical 4T tandem subject to realistic operating conditions.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Contact design; Gallium-arsenide; Multijunction solar cells; Silicon